Improving Elementary Students’ Science Literacy through the Scientific Inquiry Approach at SDN 1 Cenggu - Misbahul Janatin; Zulharman Zulharman; Arif Hidayad (Universitas Muhammadiyah Enrekang, 2025)
This study aims to improve the scientific literacy skills of fourth-grade students at SDN 1 Cenggu by using scientific literacy teaching materials. The type of research used is classroom action research. The classroom action research model used in this study is the Kemmis PTK design. This model consists of four stages: planning, action, observation, and reflection. The research instruments used in this study are tests and documentation. The technique in data analysis is using written tests in the form of multiple choices and essays to determine cognitive abilities in students' scientific literacy abilities. The results of this study indicate that there is an increase in students' scientific literacy abilities seen in cycles I and II. The results of the data analysis obtained are that in cycle I the number of students who completed was 10 people and those who did not complete were 14 people with a percentage of completion of 41.6% and incompleteness of 58.4%. In addition, in cycle II, there was an increase in completion, namely 20 students and 4 students who did not complete it, with a completion percentage reaching 83.4% and incompleteness of 16.6%. Thus, the use of the Scientific Inquiry approach can improve students' scientific literacy skills in science learning for fourth-grade students at SDN 1 Cenggu.